2003
DOI: 10.1142/s1088424603000124
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects of cobalt(II) phthalocyanine in sulfuric acid: a continuous wave and pulse EPR study

Abstract: Products based on metal phthalocyanines are widely used in industry. In the processing of these materials it is essential to control the conditions of the matrix the metal phthalocyanines are embedded in. Using the example of cobalt(II) phthalocyanine in sulfuric acid we show that continuous wave and pulse electron paramagnetic resonance and electron nuclear double resonance spectroscopy provide excellent tools to monitor the influence of the matrix on paramagnetic phthalocyanines. The g values, the cobalt hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Besides 19 F NMR, X-ray diffraction, and magnetic measurements, we use a combination of continuous-wave electron paramagnetic resonance (CW EPR), electron spin echo envelope (ESEEM), and pulsed electron nuclear double resonance (ENDOR) techniques to characterize F 64 PcCu in the solid phase and in an ethanol solution. Although X-band (9.5 GHz) CW EPR methods have been used extensively to investigate metal phthalocyanines, the application of high-field EPR , or ESEEM and ENDOR techniques to these systems is still quite limited. Some of us showed in earlier work the strength of the latter EPR methods to detect the subtle effects of the matrix and peripheral substituents on the electronic structure of PcM's (M = Cu, Co) .…”
Section: Introductionmentioning
confidence: 99%
“…Besides 19 F NMR, X-ray diffraction, and magnetic measurements, we use a combination of continuous-wave electron paramagnetic resonance (CW EPR), electron spin echo envelope (ESEEM), and pulsed electron nuclear double resonance (ENDOR) techniques to characterize F 64 PcCu in the solid phase and in an ethanol solution. Although X-band (9.5 GHz) CW EPR methods have been used extensively to investigate metal phthalocyanines, the application of high-field EPR , or ESEEM and ENDOR techniques to these systems is still quite limited. Some of us showed in earlier work the strength of the latter EPR methods to detect the subtle effects of the matrix and peripheral substituents on the electronic structure of PcM's (M = Cu, Co) .…”
Section: Introductionmentioning
confidence: 99%
“…20,22 It has been reported that the utilized solvent influences the electronic properties of the central ion for phthalocyanines, such as energies and compositions of the molecular orbitals as well as g-and A-tensors. 23,24 In these extended studies, no coherence times were published.…”
mentioning
confidence: 99%
“…Metallophthalocyanines (PcM) are a class of tetradentate macrocyclic ligands with extremely strong absorptions in the UV‐vis regions, high thermal and chemical stability, as well as a resistance to UV‐degradation [1–6] . This has driven their primary industrial use as pigments and dyes, commonly blue or green in colour [7,8] .…”
Section: Introductionmentioning
confidence: 99%